Young Mothers’ Self-Indulgence Behavior – A Qualitative Study on the Impact of Women’s Entrance into Motherhood on their Definition of Self-Indulgence, their Ability and their Will to Self-Indulge - Pramendorfer, Charlotte (2012)
This dissertation investigates young mothers’ self-indulgence behaviour. The entrance into motherhood subjects significant changes to a woman’s life. If and how these changes affect a woman’s definition of self-indulgence, her will as well as her ability to self-indulge is examined. For this purpose, eight in-depth interviews were conducted and analysed. Findings suggest mothers’ definition of self-indulgence remaining constant. Although realising the importance to self-indulge, many mothers, however, do not succeed in indulging as much as they would prefer. This is, as a major reason, found to be explained by high grades of responsibility and emotional connection experienced towards their children, leading to changes in mothers’ priorities. Moreover, the entrance into motherhood results in changes applying to a woman’s identity construction as well as challenges regarding the management of their various selves such as being a good mother, a valued employee, etc. For succeeding in offering themselves a treat, high importance was found to apply for mothers leaving their everyday setting. Moreover, ways to enhance mothers’ self-indulgence behaviour could be identified, including pre-committing to indulgence and the availability of trustworthy people taking care of their children.